STEAM, projects and computational thinking in the first years of elementary education: contributions to a disruptive education - de Almeida Rosa, Thais (2023)
This article is an excerpt from a dissertation entitled “The STEAM Approach and Project-Based Learning: The Development of Computational Thinking in the Early Years of Elementary School”, a part of the Master's Program in Management and Educational Practices at Universidade Nove de Julho (PROGEPE-UNINOVE). In this text, the objective was to show how the STEAM approach and the PBL articulated with Computational Thinking can provide pedagogical practices that contribute to the re-signification of learning in the early years of Elementary School. The research adopted a qualitative approach and was developed as an interventional study. The research object was a confessional and private school institution of Basic Education, in the North Zone of São Paulo, which has approximately 780 students enrolled, from Kindergarten to the 3rd grade of High School. A total of 48 students of the 3rd year of Elementary School between 8 and 9 years old took part in this research. The data collection instruments were as following: the questionnaire and participant observation. The main results showed that the STEAM approach articulated with the ABP and the development of Computational Thinking, provide the possibility of experiencing projects, seeking solutions that are not limited to the classroom and the school, providing new paths for a disruptive and creative education, also favoring the re-signification of learning in the early years of elementary school.